2020
DOI: 10.5535/arm.19181
|View full text |Cite
|
Sign up to set email alerts
|

A Fully Immersive Virtual Reality Method for Upper Limb Rehabilitation in Spinal Cord Injury

Abstract: Objective To determine whether a fully immersive virtual reality (VR) intervention combined with conventional rehabilitation (CR) can improve upper limb function more than CR alone in patients with spinal cord injury (SCI), we conducted a prospective, randomized, controlled clinical trial.Methods Participants were randomly assigned to either the control group (CG; n=10) or experimental group (EG; n=10). The participants in the CG received 60 minutes of conventional therapy per day, 4 days per week for 4 weeks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…Clamping power and K-SCIM score improved significantly in the experimental group after intervention. When comparing the differences between the groups, elbow extensor, wrist extensor, ASIA-UEMS, clamping power, lateral clamping power and palmar clamping power were significantly improved [56].…”
Section: Resultsmentioning
confidence: 94%
“…Clamping power and K-SCIM score improved significantly in the experimental group after intervention. When comparing the differences between the groups, elbow extensor, wrist extensor, ASIA-UEMS, clamping power, lateral clamping power and palmar clamping power were significantly improved [56].…”
Section: Resultsmentioning
confidence: 94%
“…For this reason, the evaluation process becomes essential while designing the VR-based intervention for rehabilitation. Several prior research in VR-based rehabilitation that utilize off-the-shelf VR devices did not provide performance evaluation, such as achieved range of motion (ROM), angular speed, and real-time feedback of the performed movement (Lim et al, 2020;Huang et al, 2019;Weber et al, 2019). This paper designs a system that provides a ready-to-use function for real-time upper limb movement evaluation in VR.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary evidence suggests that stroke survivors, patients on haemodialysis, following total knee arthroplasty, with spinal cord injury, and cognitive decline benefitted from VR-based interventions to a greater extent compared to conventional rehabilitation [ 13–17 ]. A recent review showed that exergaming, a form of digital-based intervention (DBI), showed promising results in enhancing strength outcomes in people with diverse health statuses compared to traditional care [ 18 , 19 ], whereas some original studies found conflicting results [ 20 , 21 ]. For the purposes of this systematic review and meta-analysis, DBI refers to those in which participants interact individually with an immersive or non-immersive digital environment generated by computers, consoles, head-mounted displays, or related devices.…”
Section: Introductionmentioning
confidence: 99%